Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia associated with bronchiectasis: A rare case - Ağababaoğlu, İsmail; Koçer, Bülent; Çetinkaya Ethemoğlu, Filiz Banu (Journal of Surgery and Medicine, 2019)
Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia is the precursor neuroendocrine tumor proliferations comprising extended focal extraluminal nodules in whole lung occasionally or limited to the bronchial or bronchiolar walls. A 30-year old patient who underwent lower left lobectomy due to the extended saccular bronchiectasis was presented. Histopathological examination of the surgical specimen revealed diffuse idiopathic pulmonary neuroendocrine cell hyperplasia associated with bronchiectasis.